2019
DOI: 10.1186/s41065-019-0092-x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the PPARD Gene and Dynamic Balance Performance in Han Chinese Children

Abstract: Background Athletic performances are complex traits with heritability of ~66%. Dynamic balance is one of the most important athletic performances, and there has been little studies for it in sports genomics. The candidate PPARD gene was reported to be able to affect muscle development for balance predisposition and influence the athletic performance including skiing triumph in the Caucasian population. This study aims to investigate whether the PPARD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
3
0
3
Order By: Relevance
“…The PPARD rs1053049 (T>C; 3′-untranslated region of exon 9) TT genotype demonstrated reduced PPARD gene expression levels 41 , higher levels of low-density lipoprotein cholesterol and increased risk of type 2 diabetes mellitus 47 , increased insulin sensitivity and decreased body mass with sports training or lifestyle intervention 26 , 48 , 49 . The PPARD rs2267668 (A>G; intron 3) AA genotype demonstrated less marked TG levels with lifestyle intervention 50 , lower dynamic balance performance 51 , higher habitual physical activity 52 , and higher peak aerobic capacity on a treadmill (VO 2 peak ) 48 . PPARD activation induces decreased TG levels coupled with up-regulation of genes related to lipid droplet secretion 52 .…”
Section: Discussionmentioning
confidence: 99%
“…The PPARD rs1053049 (T>C; 3′-untranslated region of exon 9) TT genotype demonstrated reduced PPARD gene expression levels 41 , higher levels of low-density lipoprotein cholesterol and increased risk of type 2 diabetes mellitus 47 , increased insulin sensitivity and decreased body mass with sports training or lifestyle intervention 26 , 48 , 49 . The PPARD rs2267668 (A>G; intron 3) AA genotype demonstrated less marked TG levels with lifestyle intervention 50 , lower dynamic balance performance 51 , higher habitual physical activity 52 , and higher peak aerobic capacity on a treadmill (VO 2 peak ) 48 . PPARD activation induces decreased TG levels coupled with up-regulation of genes related to lipid droplet secretion 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Šiuo metu plačiai tyrinėjamas dar vienas PPAR receptorius -PPARγ, kuris yra būtinas mioblastų ir adipocitų diferenciacijai bei yra susijęs su insulino apykaita (Barh, Ahmetov, 2019 Eynon et al, 2009). Nustatyta, kad šio polimorfizmo retasis C alelis siejamas su didesniu PPARD transkripcijos aktyvumu ir geno raiška (Cao et al, 2019). Literatūros duomenimis, PPARD polimorfizmas (C alelis) yra susijęs su padidėjusiu raumenų gliukozės įsisavinimu, lėtai susitraukiančių raumenų skaidulų kiekiu, mažesniu kūno masės indeksu (KMI) (Skogsberg, 2003).…”
Section: Rezultatų Aptarimasunclassified
“…PPARG Pro12 alelį turinčių asmenų riebalų masė, užsiimant fizine veikla, efektyviau sumažėja nei PPARG 12Ala alelio nešiotojų. Taigi, PPARG Pro12Ala polimorfizmas yra siejamas su fizinio pajėgumo fenotipu ir gali būti laikomas genetiniu veiksniu, prisidedančiu prie sportinės veiklos poligeninio profilio (Ahmetov et al, 2008; Maciejewska-Karlowska et al, 2013; Barh, Ahmetov, 2019).Kitas PPAR genų šeimos atstovas yra PPARD genas, koduojantis PPARβ/δ receptorių, kuris dalyvauja organizmo lipidų ir angliavandenių apykaitoje, energijos homeostazėje ir termogenezėje(Barh, Ahmetov, 2019;Cao et al, 2019; Trostchansky, Rubbo, 2019). PPARD reguliuoja miokardo ir griaučių raumenų gliukozės įsisavinimą ir panaudojimą, skatina mitochondrijų biogenezę.…”
unclassified
See 1 more Smart Citation
“…Mitochondrial DNA encodes some proteins of the oxidative phosphorylation enzymatic complex, playing an important role in aerobic ATP production; therefore, it can contribute to the ability to respond to endurance exercise training [49]. Both Maciejewska-Skrendo and Cao et.al, 2019 suggested that Peroxisome proliferator-activated receptor delta (PPARD) gene is associated with dynamic balance performance of human being [50,51]. Iron and Magnesium supplementation have the best quality evidence for improvements to markers and outcomes related to exercise capacity and athletic performance [39], [52,53].…”
Section: Introductionmentioning
confidence: 99%